Behaviour assessment of diesel engine operated using Butanol-Methyl Ester of Water Hyacinth blends. (2023) - Sachuthananthan, B.; Vinoth, R.; Lokeswara Reddy, P.; Naik, Gnaneswar; Sandeep, B.
Abstract: The rapid diminution of conventional fuel is steering the research towards non replenishing fuels. Alcohols, which are formed out of farming products like stalks of corn and sugarcane bagasse seems to be a encouraging non replenishing fuels. Out of various alcohol fuels, butanol has longer chain alcohol is deliberated in this attempt. This experimental attempt concentrates on the pollution and performance constraints of a Direct Injection Compression Ignition power train which uses different Butanol/Methyl Ester of Water Hyacinth (MEWH) mixtures. Trials were made with various Butanol/MEWH blends, having Butanol quantity in the mixture changing from 0 to 40% (10%, 20%, 30% and 40%-by vol. proportion mentioned as BU10, BU20, BU30, and BU40). The power train performance with various Butanol/MEWH mixtures were equated to that of Diesel. The output's exposes that as the quantity of Butanol in mixture enhanced, emission parameters like CO, HC and Soot reduced, but the NOx emanations raised substantially. Eventually, the Thermal Efficiency (BTE) of engine minimally raised with rise with butanol proportion in mixture when equated to diesel. For Diesel the BTE was found to be 29.5%, for Methyl Ester of Water Hyacinth(MEWH) the BTE was found to be 28.5%, for MEWH with 10% Butanol the BTE was 28.7%, for 20% Butanol addition, the BTE was found to be 29%, for 30% Butanol addition, the BTE was found to be 29.3% and for 40% Butanol addition the BTE is found to be 28%. The engine delivers power almost equivalent to Diesel when operated at 30% Butanol mixture.